2007
DOI: 10.1002/vnl.20109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of precipitated calcium carbonate on the mechanical properties of poly(vinyl chloride)

Abstract: were increased to 79 kJm -2 through the addition of ultra-fine pcc. The results have been interpreted in terms of the particle size, shape and coating of the calcium carbonate grades and the effect on the gelation characteristics of the PVC formulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…Fernandes and Thomas examined the effect of various grades of precipitated and ground calcium carbonate on the tensile strength and Charpy impact energy of extruded PVC profiles [81,82]. The results confirmed that especially ultrafine precipitated calcium carbonate (UFPCC) can give rise to significant improvements in single notch impact strength.…”
Section: Inorganic Impact Modifierssupporting
confidence: 59%
“…Fernandes and Thomas examined the effect of various grades of precipitated and ground calcium carbonate on the tensile strength and Charpy impact energy of extruded PVC profiles [81,82]. The results confirmed that especially ultrafine precipitated calcium carbonate (UFPCC) can give rise to significant improvements in single notch impact strength.…”
Section: Inorganic Impact Modifierssupporting
confidence: 59%
“…When the time of fusion is reduced, the melt state is reached more quickly, so the nano‐CaCO 3 particles have remained under high shear stress for a longer time, thus resulting in better dispersion of nanoparticles. Fernando and Thomas [24] showed that as the size of nano‐CaCO 3 was reduced, the time of fusion decreased. However, during fusion process, the grains of PVC are destroyed and converted into primary particle flow units, and at the time of fusion, some of these particles become submicron particles in the nanoscale range.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have investigated the effect of ultra‐fine PCC on impact properties of PVC [1–9]. Substantial improvements in impact strength have been reported depending on the PVC formulation and processing method used, as well as the PCC particle size and coating applied.…”
Section: Introductionmentioning
confidence: 99%
“…Fernando and Thomas [2] have reported that when the mean particle size of calcium carbonate is reduced below 1 μm, then there is a significant increase in the notched impact strength of filled unplasticized PVC (PVC‐U) compounds, and the smaller the particle size the greater the effect. Increasing the mean particle size above 1 μm caused a reduction in notched impact strength compared with the unfilled control.…”
Section: Introductionmentioning
confidence: 99%